Asymmetric total synthesis of smyrindiol employing an organocatalytic aldol key step - Enders, Dieter; Fronert, Jeanne; Bisschops, Tom; Boeck, Florian (Beilstein Journal of Organic Chemistry, 2012)
The first organocatalytic asymmetric synthesis of smyrindiol, by using an (S)-proline catalyzed enantioselective intramolecular aldol reaction as the key step, is described. Smyrindiol was synthesized from commercially available 2,4-dihydroxybenzaldehyde in 15 steps, with excellent stereoselectivity (de = 99%, ee = 99%). In the course of this total synthesis a new and mild coumarin assembly was developed.
Keywords: aldol reaction; asymmetric synthesis; organocatalysis; proline; smyrindiol

(untitled) - Moss, G. P.; Smith, P. A. S.; Tavernier, D. (Pure Appl. Chem., 1995)

Medical Herbalism: The Science Principles and Practices of Herbal Medicine - Hoffmann, D. (Healing Arts Press, 2003)

(untitled) - Nore, P.; Honkanen, E. (J. Heterocycl. Chem., 1980)

(untitled) - Lemmich, J.; Havelund, S.; Thastrup, O. (Phytochemistry, 1983)

(untitled) - Ngameni, B.; Kuete, V.; Simo, I. K.; Mbaveng, A. T.; Awoussong, P. K.; Patnam, R.; Roy, R.; Ngadjui, B. T. (S. Afr. J. Bot., 2009)

(untitled) - Dzhafarov, Z. R.; Kuliev, Z. A.; Vdovin, A. D.; Kuliev, A. A.; Malikov, V. M.; Ismailov, N. M. (Chem. Nat. Compd., 1992)

(untitled) - Vilegas, W.; Pozetti, G. L.; Harumi Yariwake Vilegas, J. H. (J. Nat. Prod., 1993)

(untitled) - Jiménez, B.; Grande, M. C.; Anaya, J.; Torres, P.; Grande, M. (Phytochemistry, 2000)

(untitled) - Zou, Y.; Lobera, M.; Snider, B. B. (J. Org. Chem., 2005)

(untitled) - Enders, D.; Niemeier, O.; Straver, L. (Synlett, 2006)

(untitled) - Kaur, N.; Xia, Y.; Jin, Y.; Dat, N. T.; Gajulapati, K.; Choi, Y.; Hong, Y.-S.; Lee, J. J.; Lee, K. (Chem. Commun., 2009)

(untitled) - Tsuritani, T.; Shinokubo, H.; Oshima, K. (Tetrahedron Lett., 1999)

(untitled) - Takeda, N.; Imamoto, T. (Org. Synth., 1999)

(untitled) - Krasovskiy, A.; Kopp, F.; Knochel, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Anderson, K. W.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2005)